Effect of lithofacies on pore structure and new insights into pore-preserving mechanisms of the over-mature Qiongzhusi marine shales in Lower Cambrian of the southern Sichuan Basin, China. (December 2018) - Yang, Wei; Zuo, Rusi; Jiang, Zhenxue; Chen, Dongxia; Song, Yan; Luo, Qun; Wang, Qianyou; Zhu, Hongji
Abstract: Research on shale pore structures has furthered the understanding of shale oil and gas accumulation. However, understanding of mechanisms of shale lithofacies that affect pore structures remains poor, restricting evaluations of marine shale and accurate estimations of gas content. This study focuses on the over-mature Qiongzhusi marine shales in Lower Cambrian of the Southern Sichuan Basin. A series of laboratory experiments were conducted on core samples, including X-ray diffraction (XRD), scanning electron microscopy (SEM), low-pressure gas adsorption (N2 and CO2 ) and high-pressure mercury intrusion porosimetry (MIP). XRD results show that four main types of shale lithofacies are found in the Qiongzhusi Formation according to the content of siliceous, carbonate and clay minerals, including silica-rich argillaceous shale lithofacies (SAL), argillaceous-rich siliceous shale lithofacies (ASL), carbonate/argillaceous containing siliceous shale lithofacies (C/ASL) and argillaceous/siliceous mixed shale lithofacies (A/SML). SEM images reveal that three kinds of pores within the shale samples (organic matter, intergranular and dissolved pores) with the majority being slit-like and narrow slit-like pores. Silica-rich argillaceous shale lithofacies exhibit the highest pore surface areas and volumes, while other shale lithofacies and carbonate/clay containing siliceous shale lithofacies exhibit relatively lower pore surface areas and volumes. It can be inferred that silica-rich argillaceous shale lithofacies facilitate shale gas storage and flow. Both TOC and clay mineral content are more positively correlated with the microscopic pore structure parameters of micropores than that of mesopores, and thus further interpreted as two dominant factors controlling the development and distribution of micropores. A relatively high quartz content in Qiongzhusi shale of Lower Cambrian are conductive to contribute a large macropore volume, but most importantly, the development of rigid frameworks established by authigenic quartz/pyrite and clay minerals are favorable for the preservation of primary organic matter micropores by providing effective grain supporters. Clay-rich siliceous shale could be deemed as one of the most typical lithofacies types displaying this unique pore-preserving mechanism. Shale lithofacies with different TOC and mineral compositions exhibit distinct differences in pore structures. Highlights: Whole-aperture pore structure characteristics of the Qiongzhusi shale were obtained. Lithofacies has a stronger effect on micropore structure than mesopore structure. Protective frames composed of quartz and clay minerals were found in SEM images.